Uncovering the mechanism of Clostridium butyricum CBX 2021 to improve pig health based on in vivo and in vitro studies - Liu, Xin; Qiu, Xiaoyu; Yang, Yong; Wang, Jing; Wang, Qi; Liu, Jingbo; Huang, Jinxiu; Yang, Feiyun; Liu, Zuohua; Qi, Renli (Frontiers in Microbiology, 2024)
As a symbiotic probiotic for the host, Clostridium butyricum (CB) has the potential to strengthen the body's immune system and improve intestinal health. However, the probiotic mechanism of CB is not completely understood. The Clostridium butyricum CBX 2021 strain isolated by our team from a health pig independently exhibits strong butyric acid production ability and stress resistance. Therefore, this study comprehensively investigated the efficacy of CBX 2021 in pigs and its mechanism of improving pig health. Our in vivo study showed that CBX 2021 improved growth indicators such as daily weight gain in weaned piglets and also reduced diarrhea rates. Meanwhile, CBX 2021 significantly increased immunoglobulin levels in piglets, reduced contents of inflammatory factors and improved the intestinal barrier. Subsequently, 16S rRNA sequencing showed that CBX 2021 treatment implanted more butyric acid-producing bacteria (such as Faecalibacterium) in piglets and reduced the number of potentially pathogenic bacteria (like Rikenellaceae RC9_gut_group). With significant changes in the microbial community, CBX 2021 improved tryptophan metabolism and several alkaloids synthesis in piglets. Further in vitro experiments showed that CBX 2021 adhesion directly promoted the proliferation of a porcine intestinal epithelial cell line (IPEC-J2). Moreover, transcriptome analysis revealed that bacterial adhesion increased the expression of intracellular G protein-coupled receptors, inhibited the Notch signaling pathway, and led to a decrease in intracellular pro-inflammatory molecules. Collectively, these results suggest that CBX 2021 may accelerate piglet growth by optimizing the intestinal microbiota, improving metabolic function and enhancing intestinal health.